Cover Picture: Diversification of Peptidomimetics and Oligopeptides through Microwave‐Assisted Rhodium(III)‐Catalyzed Intramolecular Annulation (Adv. Synth. Catal. 19/2019). Issue 19 (26th August 2019) - Song, Liangliang; Tian, Guilong; Blanpain, Anna; Van Meervelt, Luc; Van der Eycken, Erik V.
Abstract : The inside cover picture, designed by Liangliang Song from the group of Erik V. Van der Eycken, illustrates a chemoselective rhodium(III)‐catalyzed cascade annulation for the construction of the indolizinone and quinolizinone scaffolds. Diversification of peptidomimetics and oligopeptides is achieved in a rapid and step‐economical manner through the combination of Ugi reaction and microwave‐assisted rhodium(III)‐catalyzed intramolecular annulation via C( sp 2 )−H activation without installing a directing group. Details of this work can be found in the Communication on pages 4442–4447 (L. Song, G. Tian, A. Blanpain, L. Van Meervelt, E. V. Van der Eycken, Adv. Synth. Catal . 2019, 361, 4442–4447; DOI: 10.1002/adsc.201900550 ).